2018
DOI: 10.1590/s0100-204x2018000900010
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profile of conilon coffee brews from the state of Espírito Santo, Brazil

Abstract: The objective of this work was to present a sensory description of conilon coffee (Coffea canephora) brews produced from genotypes developed for the state of Espírito Santo, Brazil. The genotypes 'Diamante ES8112', 'ES8122', and 'Centenária ES8132' were evaluated. Nine samples from three clones (genotypes) of each cultivar, from two different regions of the state, were analyzed. A panel of tasters for coffee sensory evaluation was trained to obtain a descriptive profile and to select terms. Beverages were desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…All TSS, pH, and TTA values were within the range described for C. canephora beverages from Conilon and Robusta varieties or without variety identification: TSS between 1700 and 2539 mg 100 mL, pH between 5.32 and 6.44, and TTA between 1.05 and 4.2 mL NaOH 0.1 mol L −1 (Agnoletti et al, 2019; Kalschne, Biasuz, et al, 2019; Mori et al, 2018, 2020; Portela et al, 2021, 2022).…”
Section: Resultsmentioning
confidence: 73%
“…All TSS, pH, and TTA values were within the range described for C. canephora beverages from Conilon and Robusta varieties or without variety identification: TSS between 1700 and 2539 mg 100 mL, pH between 5.32 and 6.44, and TTA between 1.05 and 4.2 mL NaOH 0.1 mol L −1 (Agnoletti et al, 2019; Kalschne, Biasuz, et al, 2019; Mori et al, 2018, 2020; Portela et al, 2021, 2022).…”
Section: Resultsmentioning
confidence: 73%
“…The clones evaluated in this study were characterized with 38 sensory descriptors, some of them with similar characteristics, which were grouped in classes (Table 6). The descriptors are mainly associated with flavors that are found in nature (Mori et al, 2018;Pereira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Clone 66: herby, spicy, woodlike, and sweet. The study of Mori et al (2018) identified the sensory profile of the beverage of genotypes of C. canephora in the state of Espírito Santo, where the descriptors of bitterness, strong, full-bodied, astringent, and residual flavor predominated. In addition, they concluded that acidity was the attribute with the greatest impact on overall beverage quality.…”
Section: Resultsmentioning
confidence: 99%
“…When evaluating 130 accessions from a germplasm bank, Souza et al (2018) observed that up to 80% of the variability in beverage quality may be of genotypic nature. In the same line, Mori et al (2018) performed a sensory description of beverages of conilon coffee produced in Espírito Santo and observed that the cultivars Diamante 8112 and Centenária 8132 (Ministério da Agricultura, Pecuária e Abastecimento [MAPA], 2019) had superior quality according to the traditional criteria.…”
Section: Introductionmentioning
confidence: 99%